KAJIAN PENGELOLAAN SAMPAH DIKAWASAN WISATA PANTAI PARANGTRITIS KABUPATEN BANTUL - Masjhoer, Jussac Maulana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2017)
This study aims to assess the distribution and the volume of waste in Parangtritis tourism area, evaluate waste management systems that have been done by the local district, assess the effectiveness of waste management systems and assess management strategies in the Parangtritis tourism area. The method used in this research is descriptive method by using surveys. The results showed that the distribution of trash accumulating in the Mancingan Hamlet (Parangtritis Beach), Grogol IX Hamlet (Parangkusumo Beach), and Depok Hamlet (Depok Beach). The system of environmental management has been considered not effective enough and it can be seen from not yet lifted overall waste generation in a single day to a landfill. The cleaner every morning pick up the trash once a day. The availability of waste facilities and infrastructure are widely available (according to 55% of respondents) with a pretty good quality (according to 45% of respondents). In terms of financing, the levy is paid fairly in accordance with the performance of a janitor and amounts collected are found to be a burden. Local government regulations has been socialized and well implemented, but there are no articles that give strict punishment to violators. Keywords: Waste Management Strategy, Tourism Area, Coastal and Marine Environment